Rastro (2025)
This thesis addresses the essential nature of the production department, at its various levels, in the development and execution of any audiovisual project. Likewise, it serves as a practical guide to understanding and delving into the role of the production coordinator within a film project. The main objective is to explore the processes in which the production coordinator is involved during the different stages of execution in a documentary short film